2005
DOI: 10.1073/pnas.0507189102
|View full text |Cite
|
Sign up to set email alerts
|

Role for macrophage migration inhibitory factor in asthma

Abstract: Macrophage migration inhibitory factor (MIF) is an immunologic regulator that is expressed in inflammatory and autoimmune disorders. We investigated MIF's role in asthma using genetic approaches in a mouse model and in a cohort of asthma patients. Mice genetically deficient in MIF that were primed and aerosolchallenged with ovalbumin showed less pulmonary inflammation and lower airway hyperresponsiveness than genetically matched, wild-type controls. MIF deficiency also resulted in lower titers of specific IgE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
204
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(228 citation statements)
references
References 38 publications
16
204
8
Order By: Relevance
“…Consistent with this data, MIF levels were significantly lower in colonic tissue and sera in TRX-Tg mice in a mouse model of acute DSS-induced colitis [32]. Recent studies indicate that MIF plays an essential role in the pathogenesis of allergic airway inflammation [3][4][5][6]. Upon allergen sensitization and challenge, mice lacking MIF exhibit reduced AHR, tissue eosinophilia, and mucus metaplasia with concomitant decreases in levels of eotaxin and IL-13 in BALF.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Consistent with this data, MIF levels were significantly lower in colonic tissue and sera in TRX-Tg mice in a mouse model of acute DSS-induced colitis [32]. Recent studies indicate that MIF plays an essential role in the pathogenesis of allergic airway inflammation [3][4][5][6]. Upon allergen sensitization and challenge, mice lacking MIF exhibit reduced AHR, tissue eosinophilia, and mucus metaplasia with concomitant decreases in levels of eotaxin and IL-13 in BALF.…”
Section: Discussionsupporting
confidence: 73%
“…Recent studies suggest that MIF may play a key role in the pathogenesis of airway inflammation [3][4][5][6]. Therefore, we next examined the lungs of TRX-Tg and WT mice for differences in MIF expression in our model of asthma.…”
Section: Reduced Production Of Mif By Lung Epithelial Cells From Trx-mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that MIF regulates the activation of T cells induced by mitogenic or antigenic stimuli, inducing IL-2 secretion and lymphocyte proliferation [31,34]. In fact, MIF -/-mice have a reduced spleen T cell-proliferative response upon OVA restimulation [34]. We also observed that restimulation of spleen cells with OVA caused a reduced proliferative response and IL-13 production in allergensensitized and challenged MIF -/-mice compared to WT mice (Fig.…”
Section: Involvement Of Mif On Antigen-specific Responsessupporting
confidence: 56%
“…A recent study demonstrated that MIF -/-mice lack the cardinal features of asthma and display a reduction of IL-4, IL-5 and eotaxin amounts in the lung 16 h after the last challenge [34]. Considering the essential role of Th2 cytokines in eosinophilic inflammation, mucus metaplasia and AHR, and the lack of these features in MIF -/-mice, we measured the concentrations of IL-4, IL-5 and IL-13 in the BALF 6 h after the last challenge.…”
Section: Mif Regulates Production Of Inflammatory Mediators In the Almentioning
confidence: 99%